POLA DISTRIBUSI DAN KUALITAS AIR LINDI DI LINGKUNGAN TPA BANJARSARI - Revaputri Sugianti; Nindy Callista Elvania (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
The increasing volume of waste in Bojonegoro Regency has led to increased leachate production at the Final Processing Site, particularly the Banjarsari Landfill, which has the potential to cause environmental pollution. This study aims to analyze leachate distribution patterns and evaluate leachate quality around the Banjarsari Landfill. The research method includes direct measurements at 13 observation points to determine the acidity (pH), temperature, and soil moisture values. Leachate samples were also taken at the inlet and outlet of the treatment plant for analysis based on the parameters of pH, BOD, COD, TSS, total nitrogen, and the heavy metals cadmium (Cd) and mercury (Hg). The results showed that the soil pH ranged from 4.5–7.0 and the soil temperature between 28–37°C, with variations at each observation point. Some locations showed more acidic conditions suspected to be influenced by leachate seepage. Leachate distribution was identified as uneven and influenced by distance from the source, soil moisture, and groundwater flow direction. The results of quality tests showed a decrease in pollutant concentration after treatment, so the leachate treatment system is considered effective and meets applicable quality standards.